Domestication of Women: A Reciprocal Hermeneutic Study of Faqihuddin Abdul Kodir and Huzaimah Tahido Yanggo - Qonita, Alfi; Ilyas, Hamim (Millati: Journal of Islamic Studies and Humanities, 2024)
This article aims to look at the portrait of the role of women both in the public and domestic. This Research is comparing the thoughts of Faqihuddin Abdul Kodir and Huzaemah Tahido Yanggo with their expertise that upholds the spirit of egalitarian and justice. The research is literature using a reciprocal hermeneutic approach. Reciprocal or often called mubadallah has the characteristics of returning to the text, context and contextualizing in life. Some of the principles used in this approach are to look for the main message in the text and ignore subjects/objects that point to a particular gender, so that all laws can apply equally. The dual role in this study is often experienced by women (it can also happen to men) because they do domestic work while working in the public sphere. This will be a big problem in every household if a family does not apply the concept of 'parallelism'. Both the thoughts of Faqihuddin Abdul Kodir and Huzaemah T. Yanggo use the concept of reciprocity when reading texts from both the Qur'an and hadith with relationships, so that the message of 'cooperation' and partners built in the relationship between men and women can be built in everyday life.